DIGITALIZATION OF EDUCATIONAL CONTENT IN THE CONTEXT OF DISTANCE LEARNING: THE READINESS OF STUDENTS AND TEACHERS - Khramtsov, Ivan; Askarova, Gulnara; Sabekia, Raushana; Goncharov, Vitaly; Bodrova, Tatyana (Revista Inclusiones, 2020)
Digitalization of all sectors of the economy, the implementation of digital technologies in all spheres of life open up unsurpassed opportunities for economic development and, as a result, improve the quality of citizens’ life. Digital technologies provide an opportunity to intensify the educational process, improve the level and quality of perception, understanding, and assimilation of knowledge. The article provides a theoretical analysis of the problems and prospects of the digitalization of educational content in the context of distance learning. Based on an expert survey, the main types of digital educational content used in distance learning were identified. In the course of empirical research, the authors performed diagnostics of readiness of students to distance learning using digital learning resources, as well as the teachers’ readiness for professional self-improvement in the implementation of digital educational content (DEC) in the learning process.